Community Mapping and Theory of Planned Behavior as Study Tools for Solid Waste Management. (21st August 2014) - Apinhapath, Chainarong
Abstract : Many cities have encountered problems with uncollected solid waste. Separate disposal of recyclable waste is viewed as the most effective procedure in waste management. However, this requires the cooperation of the people in the community. Community mapping is the most effective tool for understanding a community but it does not address possible ways to change people's behavior. The Theory of Planned Behavior was the basis for this study of recycling behavior as it offers methods for changing people's habits. However, the theory does not provide guidance on how to facilitate the use of recycling bins in the community. Many recycling projects have been unsuccessfully implemented due to the fact that most people do not want waste bins placed near their houses. Therefore, both of these effective tools were combined in this study, which propose an effective implementation method for community solid waste management.